Effects of long-term vitamin D supplementation on metabolic profile in middle-aged and elderly patients with type 2 diabetes. Issue 225 (January 2023) - Hu, Zhiyong; Zhi, Xueyuan; Li, Jiafu; Li, Bingyan; Wang, Jinxiu; Zhu, Jianliang; Zhang, Zengli
Abstract: To evaluate the effects of long-term vitamin D supplementation on metabolic profiles in middle-aged to elderly patients with type 2 diabetes (T2D), a randomized controlled trial was conducted among patients with T2D aged 50–70 years. A total of 270 patients underwent randomization with 135 being allocated to the vitamin D group and 135 to the control group, and participants in the vitamin D group received oral vitamin D3 (800 IU/day) for 30 months. Serum 25(OH)D and metabolic variables were measured at baseline, and after 6, 12, 18, and 30 months of intervention. After 30 months, the vitamin D group showed a greater increase in serum 25(OH)D than the control group (12.39 ± 6.99 vs 5.35 ± 5.29 ng/ml, P  < 0.001). Meanwhile, changes in the levels of fasting insulin, HOMA-IR, non-high-density-lipoprotein cholesterol (non-HDL-C), high-sensitivity C-reactive protein (hs-CRP), and uric acid differed significantly between the two groups (all P  < 0.05). Stratified analysis indicated that change in uric acid differed significantly between the two groups in subgroup with baseline 25(OH)D ≥ 20 ng/ml ( P  = 0.042) or subgroup with female patients ( P  = 0.034). And the change in fasting blood glucose (FBG) differed significantly between the vitamin D group (−0.30 ± 2.52 mmol/L) and the control group (0.49 ± 1.78 mmol/L, P  = 0.049) among patients achieving 25(OH)D concentrations of 30 ng/ml at the end of this trial. A significant difference in the change of triglyceride was observed between the two groups among patients with obesity at baseline [0.05(−0.59, 0.23) vs 0.41(−0.01, 0.80) mmol/L, P  = 0.023]. These findings suggested that long-term vitamin D supplementation significantly reduced fasting insulin, HOMA-IR, and serum concentrations of non-HDL-C, hs-CRP, and uric acid among middle-aged to elderly patients with T2D. And vitamin D status, gender, and baseline obesity may modify the effects of vitamin D supplementation. Highlights: Daily 800 IU vitamin D supplementation for 30-month is safe for T2D patients. Vitamin D improved glycemic control, lipid profiles, and uric acid levels. Vitamin D status, gender, and body mass index modify the effects of vitamin D supplementation. Vitamin D did not affect blood pressure, adiposity measures, or osteocalcin levels.